PENERAPAN TERAPI GENERALIS PADA PASEN SKIZOFRENIA DENGAN MASALAH KEPERAWATAN HALUSINASI PENDENGARAN - Nur Syamsi Norma Lalla; Wiwi Yunita (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2022)
Application of generalist therapy in Schizophrenic Patients with Nursing Problems Hearing Hallucinations Auditory hallucinations are hearing voices or noises that are less clear or clear, where sometimes these sounds are like talking to the patient and sometimes ordering the patient to do something. If auditory hallucinations cannot be controlled, it can result or impact injuring oneself, others and the environment. The purpose of this case study is to determine the implementation of generalist therapy in schizophrenia patients with auditory hallucinations nursing problems at the Avicenna Clinic Makassar. This scientific paper uses a case study method design with a nursing process approach consisting of assessment, diagnosis, intervention, implementation and evaluation of nursing. The data collection technique was carried out through interviews and observations at the Avicenna Clinic in Makassar which was carried out on 27-30 December 2021.